Field notes contributed by Joseph P. Schaufenbuel, spring 1979 - Schaufenbuel, Joseph P.et al (1979)
Spring report of birds and locations contributed by Joseph P. Schaufenbuel. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1979. Epson - sheet feed/flatbed